The multiple chronological techniques applied to the Lake Suigetsu SG06 sediment core, central Japan. (28th September 2012) - Staff, Richard A.; Nakagawa, Takeshi; Schlolaut, Gordon; Marshall, Michael H.; Brauer, Achim; Lamb, Henry F.; Bronk Ramsey, Christopher; Bryant, Charlotte L.; Brock, Fiona; Kitagawa, Hiroyuki; van der, Johannes; Payne, Rebecca L.; et al.
<x xml:space="preserve">Abstract</x> The varved sediment of Lake Suigetsu (central Japan) provides a valuable opportunity to obtain high‐resolution, multi‐proxy palaeoenvironmental data across the last glacial/interglacial cycle. In order to maximize the potential of this archive, a well‐constrained chronology is required. This paper outlines the multiple geochronological techniques being applied – namely varve counting, radiocarbon dating, tephrochronology (including argon–argon dating) and optically stimulated luminescence (OSL) – and the approaches by which these techniques are being integrated to form a single, coherent, robust chronology. Importantly, we also describe here the linkage of the floating Lake Suigetsu (SG06) varve chronology and the absolute (IntCal09 tree‐ring) time scale, as derived using radiocarbon data from the uppermost (non‐varved) portion of the core. This tie‐point, defined as a distinct (flood) marker horizon in SG06 (event layer B‐07–08 at 1397.4 cm composite depth), is thus derived to be 11 255 to 11 222 IntCal09 cal. years BP (68.2% probability range).